Difficulty in management of intraductal papillary mucinous neoplasm-associated pancreatobiliary fistulas and the role of “pig-nose” appearance and intraductal ultrasonography in diagnosis - Koizumi, Mitsuhito; Kumagi, Teru; Kuroda, Taira; Azemoto, Nobuaki; Yamanishi, Hirofumi; Ohno, Yoshinori; Yokota, Tomoyuki; Ochi, Hironori; Tange, Kazuhiro; Ikeda, Yoshiou; Hiasa, Yoichi (Endoscopy International Open, 2016)
Pancreatobiliary fistulas associated with intraductal papillary mucinous neoplasms (IPMN) often develop obstructive jaundice and cholangitis; thus, early diagnosis is important. However, computed tomography and cholangiography, the current methods for detecting pancreatobiliary fistulas, are not always effective. We previously reported a case of IPMN-associated pancreatobiliary fistula and proposed a potential new diagnostic marker: the “pig-nose” appearance of the duodenal papilla, which results from dilated pancreatic and bile ducts and can be visualized via endoscopy. In this study, we report another three cases of IPMN-associated pancreatobiliary fistulas detected by a different technology, intraductal ultrasonography (IDUS). As with our previously reported case, we confirmed the utility of the “pig-nose” appearance and IDUS in the diagnosis of IPMN-associated pancreatobiliary fistulas. In addition, we found it difficult to manage biliary obstruction that resulted from the flow of mucinous material through pancreatobiliary fistulas. The obstruction was treated with endoscopic nasal biliary drainage (ENBD), but this was not always successful. In two of our cases, additional treatment with a large diameter fully covered metal stent failed to improve jaundice. Therefore, we conclude that standard endoscopic stenting may not be effective, and that alternative endoscopic methods or surgery may be necessary.